An Application of the Generalized Method of Moments on the Mankiw-Romer-Weil Model - CHAKRABORTY, Arpan; CHATTOPADHYAY, Siddhartha; SAHU, Sohini (Theoretical and Practical Research in Economic Fields; Vol 16 No 3 (2025): TPREF, Volume XVI, Issue 3(35), Fall 2025DO - 10.14505/tpref.v16.3(35).01, 2025)
This paper develops an algorithm for the restricted Generalized Method of Moments (RGMM) to re-evaluate the empirical findings of Mankiw, Romer, and Weil (1992), who emphasized the critical role of human capital accumulation in explaining cross-country income differences. Despite the influence of their results, subsequent literature has raised concerns about potential endogeneity arising from omitted variable bias. To address these concerns, we employ a novel instrumental variable strategy - using the algorithm of the restricted Generalized Method of Moments (RGMM). Using the restricted GMM, we find that the original Mankiw, Romer, and Weil (1992) results are robust for the method of estimation and survive the endogeneity criticisms that are present in the literature.